Timber-concrete composite connections using GFRP notches fastened with self-tapping screws: Conceiving, numerical modelling and testing. (2nd August 2021) - Marchi, Luca; Pozza, Luca
Highlights: A connector for TCC structures involving a GFRP notch and screws was investigated. Eccentricity effects caused by an interlayer were analyzed via detailed FE models. Concrete failure was avoided inspite of using high load-bearing capacity screws. Use of light-weight concrete cause negligible effects on resistance and stiffness. Injection moulded GFRP components may enhance the use of timber screws. Abstract: In the structural engineering field, injection moulded Glass Fibre Reinforced Polymer (GFRP) components are typically used as parts or accessories of fastening systems. In this paper, an extended numerical and experimental study on a Timber-Concrete Composite Connection (TCCC) realized with an injection-moulded GFRP notch fastened to the timber beam with self-tapping screws is presented. Numerical simulations performed to predict the performance of the investigated TCCC in terms of force-displacement curves are compared with the outcomes from forty push-out tests. Results demonstrate how the GFRP notch assure the full exploitation of the screws withdrawal capacity without incurring in sudden concrete failures independently from the type of concrete used (normal and light-weight).